Finite element study on the micromotion of cementless total hip arthroplasty - Mohd. Yusof, Baharuddin; Mohammed Rafiq, Abdul Kadir (International Federation for Medical and Biological Engineering, 2011)
Link to publisher's homepage at www.ifmbe.org/